2009
DOI: 10.1074/jbc.m806633200
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Cellular Activation Studies Reveal That Toll-like Receptor 2 Can Differentially Recognize Peptidoglycan from Gram-positive and Gram-negative Bacteria

Abstract: Although much progress has been made toward the identification of innate immune receptors, far less is known about how these receptors recognize specific microbial products. Such studies have been hampered by the need to purify compounds from microbial sources and a reliance on biological assays rather than direct binding to monitor recognition. We have employed surface plasmon resonance (SPR) binding studies using a wide range of well defined synthetic muropeptides derived from Gram-positive (lysine-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Previously, it has been shown that TLR2 can differentially recognize peptidoglycans from Gram-positive and Gram-negative bacteria (35). Moreover, recent reports suggest that Sb S LD (AG83) may deactivate the host TLR2 signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that TLR2 can differentially recognize peptidoglycans from Gram-positive and Gram-negative bacteria (35). Moreover, recent reports suggest that Sb S LD (AG83) may deactivate the host TLR2 signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Known Francisella TLR2 agonists include the uncharacterized lipoproteins LpnA/Tul4 and FTT_1103 (86,220). To our knowledge, TLR2 recognition of Francisella PGN has not been reported, and the status of PGN as a TLR2 ligand is still under debate (12,73,222). Several reports have shown that TLR2 is essential for the early inflammatory response to Francisella infection in macrophages in vitro, as well as a critical component of the host response to in vivo Francisella infection as demonstrated by its requirement for control of pulmonary and intradermal infection (1,16,55).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…These transcriptional regulators induce the expression of inflammatory cytokines and type I interferons, resulting in the activation of innate and adaptive immune cells (109,115). Numerous TLRs recognize bacterial PAMPs, including TLR2, which senses bacterial lipoproteins (BLPs) and peptidoglycan (PGN) (12,73), TLR4, which signals in response to LPS from Gramnegative bacteria, TLR5, which recognizes flagellin, and TLR9, which senses bacterial CpG DNA (115).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…A canonical member of this family is the asparagine synthase of Escherichia coli , AsnB (Huang et al ., 2001). PG recognition by the mammalian host innate immune system has been shown to be affected by amidation of mDAP (Asong et al ., 2009; Girardin et al ., 2003) but the physiological role of mDAP amidation in the homeostasis of the bacterial cell wall remains unknown. PG synthesizing enzymes seem to work as efficiently on amidated as in non‐amidated mDAP in both L. plantarum and C. glutamicum (Bernard et al ., 2011b; Levefaudes et al ., 2015), suggesting that mDAP amidation may not be necessary for efficient cell wall synthesis (Levefaudes et al ., 2015; Hirasawa et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%